Effect of different irrigation levels on yield, water use efficiency and some quality parameters of tomato - Yavuz, Muharrem Yetis; Yildirim, Murat; Camoglu, Gokhan; Erken, Okan (2007)
The study determined the effect of water stress on yield and quality of field grown tomato (Lycopersicon esculentum cv. Mona F1) irrigated by a drip irrigation system and evaluated its water use efficiency. The amount of irrigation water applied was based on cumulative evaporation from a Class-A pan. Changes in fruit quality were determined by applying drip irrigation at different levels on Mona F1 tomatoes grown at the Irrigated Agriculture Research Center, Canakkale University, in Canakkale, Turkey in 2002 and 2003. Irrigation treatments consisted of five plant-pan coefficients (Kcp1 = 0.25, Kcp2 = 0.50, Kcp3 = 0.75, Kcp4 = 1.00 and Kcp5 = 1.25). The shortest irrigation interval (5 d) was applied at the second stage of crop growth in 2002 and at the third stage in 2003. The highest yield was obtained in Kcp4 for both years. The average values for total water use efficiency (TWUE), irrigation water use efficiency (IWUE) and the ratio of the applied irrigation water to crop water consumption (IR/ET) were 1.05 kg ha-1mnr-1, 1.12 kg ha-1 and 0.4, respectively. Yield response factor (ky) for the entire growth period was 0.60. Our results showed that quality parameters such as soluble solid concentration, fruit firmness, titratable acid and pH decreased with an increase in the amount of irrigation water.
Keywords: Irrigation management; Tomato farming